FREE ACCESS TO JUSTICE AND PROCEDURAL LIABILITY - Lucas Pahl Schaan Núñez (Revista Eletrônica de Direito Processual, 2018)
The essay proposes a rational analysis of the procedural law wich grants free access to the legal system to those who can‟t afford it, proposing that the effects of the decision wich grants this benefit should be restricted in order to guarantee wide access to justice without exempting the defeated party of its procedural liability.